In-Situ Tests on Silica Aerogel-Based Rendering Walls - Inês Flores-Colen (2020)
In this paper, two aerogel-based renders are characterized based on in-situ testing of walls prototypes. The in-situ tests to assess the mechanical performance are: pull-off, surface impact tests and compressive strength on collected samples. The physical performance includes the water resistance and thermal conductivity coefficient. The tests carried out to assess water-resistance are: Karsten tube, moisture meter and capillary water absorption of collected samples. The thermal performance was tested based on infrared thermography and thermal conductivity transient method. The combination of these in-situ tests allowed a better performance characterization of the aerogelbased renders and characterized the applied renders. These results were carried out under two national research projects (Nanorender and P2020 PEP).